Media Sosial dan Citra Merek Rumah Karya Indonesia dalam Meningkatkan Daya Tarik Wisata Tao Silalahi, Kabupaten Dairi - Hengky Pramudia Ujung; Marlon Sihombing; Onan Marakali Siregar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to analyze the role of social media marketing and the brand image of Rumah Karya Indonesia (RKI) in increasing the tourism attractiveness of Tao Silalahi, Dairi Regency. The research employed a qualitative approach using a descriptive method. Data were collected through interviews, observations, and documentation involving RKI management, local communities, and tourists. The findings indicate that social media marketing, particularly through Instagram, plays a significant role in enhancing destination visibility and tourists’ visit intentions through engaging visual content, appropriate audience segmentation, and community collaboration supported by word-of-mouth marketing. In addition, RKI’s brand image is positively shaped by the provision of authentic tourism experiences based on arts and culture, inclusive community-based services, affordable activity pricing, and creative as well as collaborative promotional strategies. The integration of social media marketing and brand image contributes to strengthening the tourism attractiveness of Tao Silalahi in terms of natural, cultural, activity-based, and supporting infrastructure aspects. This study highlights that digital marketing strategies rooted in cultural values and local community involvement are effective approaches for sustainable tourism destination development.